Violência nas relações íntimas: uma análise psicossociológica - Souza, Ana Angélica Pereira (2010)
Violence against women in the context of intimate relationships is that practiced by the spouse, fiance, boyfriend or partner. It is the most recurrent type of violence against women. The aim of this study was to investigate factors related to permanence and the disruption of intimate violence from the perspective of women in situations of violence. The research was to first build a theoretical model to explain the start, stay and disruption of the violent relationship, and then was carried out empirical research addressing the theoretical model. The theoretical model considers that violence in intimate relationship can be analyzed from three dimensions: the cognitive dimension, in which the main factor explaining the maintenance of violent intimate relationship would be the cognitive dysfunction, consisting of features such as dysfunctional beliefs / irrational, low self-esteem, low perceived self-efficacy, external locus of control, the relational dimension, mainly formed by the behavioral feature of the relationship, ie, the assessment made by the wife of the "gains" in keeping the relationship and their losses if she would break the relationship - economic dependence, concern for the livelihood or welfare of children, rejection of the status of women separate, fear of being murdered, and the cultural dimension, formed by broad social beliefs about violence, sex roles , reflected in perceived social support by women, either by groups closer as family and friends, or social institutions, police, justice, among others. The empirical research consisted of a multiple case study with 12 women who lived or still live in a violent intimate relationship. The instrument of data collection was an in-depth interviews conducted in two parts. At first the woman had a history of violent relationships and were second in depth specific issues related to the model. Data analysis showed that indicators of cognitive dysfunction were present mainly during the stay of women in violent relationship, the main dysfunctional belief checked was the belief of women, often for years, in changing the behavior of the violent partner. The behavioral feature was evident on a continuation and disruption. The functional aspect was the most frequent maintenance by the husband of the household expenses and / or children. Two types of cracking the behavioral feature were more indicated as causes of the disruption - the woman started to have conditions to maintain and keep their children without the need of the partner, and the woman suffered an assassination attempt. Social support from family and friends to the relationship was motivating to stay and in some cases the non-perception of social support also favored the retention. Concerning the social support for the disruption, there was emphasis on the social support of children, cited as decisive as significant part of women. One reference was also a lack of social support institutions - the police and justice - as motivators of stay. In one case this lack of support led to a reworking cognitive stronger dysfunctional beliefs that women should remain in violent relationships. The mechanisms of relational and cultural dimensions were more influential in breaking, while the cognitive characteristics appear to be associated with more permanence